IMPLEMENTASI KEBIJAKAN PROGRAM JAMINAN KESEHATAN KRAMA BADUNG SEHAT (KBS) DI KABUPATEN BADUNG - Tarini, Ketut Bella; Putri Wirantari, I Dewa Ayu; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2020)
ABSTRACT Various health insurance program innovations were created by the central government or regional governments. Like one of them the Badung Regency Government, created an innovative health insurance program to the whole community through the KBS program. The purpose of this study was to see how the implementation of the KBS health insurance program policy in Badung Regency. This study used descriptive qualitative research methods. KBS program which is measured according to Charles.O Jhones by using 3 indicators, namely the organization has been running well but there are still deficiencies such as infrastructure. Second, Interpretation has not run optimally due to lack of socialization to the community. Application has not been going well because there are obstacles in mobilizing the population in the South Badung area so that card distribution is hampered.From these problems, of course the need to hold socialization and pick up the ball back to the community. Keyword : Implementation, Health Insurance, Krama Badung Sehat.